Evaluation of efficacy of whatsapp messenger application in medical research education - Mulkalwar, Alhad A.; Dashputra, Amit V.; Jaipuri, Afrid T.; Sutar, Pallavi V.; Mulkalwar, Sarita A.; Rathod, Hetal (International Journal of Research in Medical Sciences, 2019)
Background: There is lack of knowledge regarding research amongst medical students as it is not included in the present curriculum of MBBS. Hence authors have selected ‘Medical Research’ as a topic to evaluate the efficacy of WhatsApp messenger application as a teaching-learning tool. There is very limited research on impact of technological modalities like WhatsApp on education. Authors undertook this study to evaluate its efficacy as a tool to supplement medical research education and assess the perception of students about e-learning via WhatsApp messenger application. Methods: A prospective analytical interventional study was conducted after obtaining ethical approval from the Institutional Ethics Committee. A self-designed comprehensive questionnaire was used to test the knowledge of medical students. A series of modules were sent and discussed on the WhatsApp study groups followed by assessment in change of the level of knowledge amongst the participants post intervention. Results: Applying the paired t-test, the scores of the study participants showed a statistically significant increase in the post- intervention evaluation (Mean=10.13, Median=10, Range=0-21) as compared to the baseline knowledge regarding medical research as reflected in the pre intervention evaluation (Mean=6.76, Median=7, Range=0-16). Conclusions: Growing availability of economical and user friendly smart phones in every generation has promoted use of WhatsApp by teachers as well as students. WhatsApp has the potential to supplement academic learning and become a natural educational modality. Necessary precautions could be taken to minimize the drawbacks expressed by the students to make it a more enjoyable and acceptable tool for teaching and learning.